Fluorinated naphtho[1, 2-c:5, 6-c']bis[1, 2, 5]thiadiazole-containing π-conjugated compound: synthesis, properties, and acceptor applications in organic solar cells. (October 2018) - Chatterjee, Shreyam; Ie, Yutaka; Seo, Takuji; Moriyama, Taichi; Wetzelaer, Gert-Jan; Blom, Paul; Aso, Yoshio
Abstract The incorporation of electron-accepting units into π-conjugated systems is well-established as a powerful approach to tune the physical properties and frontier orbital energy levels of molecules. To realize semiconductors with novel functions, naphtho[1, 2-c :5, 6-c ']bis[1, 2, 5]thiadiazole (NTz ) has been utilized as an effective electron-accepting unit. To enhance the electron-accepting nature ofNTz in this work, the synthesis of fluorinated naphthobisthiadiazole (FNTz ) was accomplished by the sequential introduction of amino functional groups into 1, 5-difluoronapthalene derivatives to form fluorinated tetraaminonapthalene derivatives, followed by the formation of thiadiazole rings. Organic solar cells based on our synthesizedFNTz acceptor in combination with poly(3-hexylthiophene) (P3HT) as a donor exhibit a significant improvement of power conversion efficiency (PCE) compared to the corresponding nonfluorinatedNTz -based cells, reaching a high PCE of up to 3.12%. Investigation of the blend-film properties and device physics unambiguously reveals that the blend films based on P3HT and theFNTz -based compound shows good film morphologies and thus efficient charge generation and transport characteristics. These results demonstrate the potential ofFNTz for an electron-accepting unit in organic semiconductors. Organic solar cells: Tweaking carbon-based rings for greater efficiency A procedure that adds fluorine atoms to carbon-based ring systems can make it easier to optimize low-cost solar cells. Organic photovoltaics normally contain junctions between electron-rich 'donor' molecules and 'acceptor' compounds able to accommodate negative charges. Yutaka Ie from Osaka University in Japan and colleagues have found that modifying acceptor compounds so that they capture more electrons enhances solar energy conversion efficiency in organic devices. The team accomplished this with a multi-step synthesis that converts ordinary naphthalene rings into rings containing fluorine, the strongest electron-attracting element in the periodic table, nitrogen and sulfur. Combined microscopy and photovoltaic measurements revealed that the fluorine atoms, which impart Teflon-like properties to many molecules, helped the new acceptor blend smoothly with donor molecules into the active layer of a thin-film device. A new electron-accepting π-conjugated compound containing fluorinated naphthobisthiadiazole (FNTz) is designed and synthesized for application as an acceptor in organic solar cells (OSCs). Physical measurements show that the introduction of fluorine atoms in the naphthobisthiadiazole (NTz) unit has considerable influence on the absorption behavior and frontier orbital energy levels of molecules. In OSCs, the FNTz-based acceptor in combination with poly(3-hexylthiophene) (P3HT) as a donor exhibits a significant improvement in power conversion efficiency compared to the corresponding nonfluorinated NTz-based acceptor. This study demonstrates the potential of FNTz as an electron-accepting unit in organic semiconductors.